Population dynamics, changes in land management, and the future of mountain areas in Northern Caucasus: The example of North Ossetia - Gracheva, Raisa; Kohler, Thomas; Stadelbauer, Jörg; Meessen, Heino (ERDKUNDE, 2012)
This study deals with population dynamics in the mountains of North Ossetia-Alania (Russian Federation) over the last 120 years. It documents the loss of mountain population over this period and analyses its implications on demography and land use. The combined processes of growth in the piedmont and outmigration from the mountains have led to a drop in the proportion of the mountain population within the Republic from 20% in 1900 to 1% in 2010. Most of the population loss in the mountains occurred before 1989 and was due to forced as well as opportunity-based migration. The key demographic effects of this exodus are a lack of young people and overrepresentation of old people in mountain communities, with an old-to-young-age dependency ratio of 1.42, which is very high in international comparison. Outmigration and social change led to the abandonment of the majority of mountain settlements and of traditional land management, posing a threat to cultural heritage. The current open-access grazing regime leads to overuse of easily accessible pastures and underuse of more remote grazing areas. Bush and forest encroachment are visible on remote pastures within the montane zone, and first stages of the process are also evident in subalpine meadows. Mountain development is at a crossroads today. The survival of the remaining communities seems uncertain in spite of an emerging interest in mountains and mountain recreation among the urban population. Official development plans focus on resort-based tourism and hydropower generation, thus serving mainly lowland interests. The methods used for this study include a literature review, use of official statistics from different administrative levels, and five field campaigns from 2006 to 2010 for ground truthing, local data collection and survey, and for conducting interviews and informal discussions with officials and administrators at different levels, and mountain residents.